Globalisation processes and tourism industry development in North-East Asia (Korea, China, Japan) - Kan, Den Sik; Vasylchuk, Volodymyr M.; Chuprii, Leonid V.; Datskiv, Igor B.; Kravets, Kateryna P. (Linguistics and Culture Review, 2021)
The paper covers relevant issues, such as the current state of the tourism services sector in China, Japan, and South Korea. The significance is confirmed by the growing role of the North-East Asian countries in the world trade in services and the growing contribution of tourism to the global gross domestic product. The purpose of this study is to identify the features, problems, and prospects for the development of the tourism services sector in China, Japan, and South Korea. The paper uses methods of systematisation and typification, which made it possible to determine the specifics of the development of cultural tourism in the Far Eastern region among the current range of opinions and areas of cultural tourism research. The study uses the principles of historicism and objectivity, which allowed analysing the development and current state of tourist exchange. A cultural approach was also used to reconstruct the cultural and humanitarian population of North-East Asia through the mutual enrichment of nations and people. The systematic approach made it possible to understand the importance of humanitarian exchange between people and identified the universality of tourism.